An analysis of the 24-hour on-call experience and treatment decision of a dental resident, a retrospective study - Jiaoer Zheng; Ji Xu; Denghui Zhang (PeerJ)
Objectives To analyze the 24-hour on-call experience and factors influencing the treatment decisions of a dental resident for dental emergencies, particularly pulpitis, during on-call hours. Methods This retrospective study was conducted at a public stomatology hospital from January 1 to December 30, 2023. Each consultation was documented, recording the date and time, patient age and gender, diagnosis, and any emergent interventions. Statistical analyses were conducted using univariate analysis to explore the association between various factors and the incidence of dental interventions for pulpitis, with significance set at p < 0.05. Results Over 1 year, 81 residents from seven specialties managed 2,717 consultations during 365 instances of 24-h call duty. The busiest months were October (n = 297). Most consultations occurred during extended hours (1,856 consultations) compared to normal hours (8:00–17:00) (861 consultations). The busiest consultation periods were between 20:00 and 22:00. Pulpitis was the most frequently diagnosed condition (n = 988). Univariate analysis showed no significant impact of patient gender (p = 0.896) or age (p = 0.632) on the likelihood of receiving a dental intervention. However, consultations during extended hours were twice as likely (OR = 2.028, 95% CI [1.510–2.723]) to result in no intervention compared to normal hours. Endodontics and pediatric dentistry residents were more likely to perform interventions compared to other specialties, with postgraduate year (PGY) six residents being less likely to perform interventions compared to PGY4 residents. Conclusion Residents exhibit lower willingness to perform dental interventions during extended working hours and in higher grade levels, with significant variability across different specialties. Enhanced training and fatigue risk management for residents may help to ensure effective patient care during on-call hours.